Pengaruh Kualitas Makanan dan Pelayanan Terhadap Kepuasan Tamu di Restoran Kura-Kura pada Oberoi Beach Resort Bali - Paramita, Kadek Herdina Pradnya; Dewi, Desak Made Purnama; Suriyani, Ni Nyoman Ayu (Jurnal Mosaik Hospitaliti, 2025)
This study aims to determine the effect of food quality and service quality on guest satisfaction at Kura-Kura Restaurant, located in the Oberoi Beach Resort Bali. The background of the research emphasizes the importance of food and service quality as crucial factors influencing customer satisfaction in luxury restaurant settings. The research uses a quantitative method with data collected from 70 respondents through a structured questionnaire. The data were analyzed using multiple linear regression with the support of SPSS version 22. Preliminary tests including validity, reliability, and classical assumptions (normality, multicollinearity, and heteroscedasticity) were also conducted. The results show that both food quality and service quality have a positive and significant effect on guest satisfaction, both partially and simultaneously. Among the two variables, service quality has the more dominant influence, with a standardized coefficient of 0.263 compared to 0.240 for food quality. This suggests that while both aspects are important, improving service quality has a slightly stronger impact on enhancing guest satisfaction. The coefficient of determination (R²) indicates that 33.9% of guest satisfaction is explained by the two independent variables studied, while the remaining 66.1% may be influenced by other factors not included in this research. The study concludes that maintaining high standards in both food and service quality is essential for guest satisfaction. Therefore, it is recommended that the restaurant management conduct regular customer satisfaction surveys, maintain consistency in food quality, and invest in continuous staff training to enhance service performance.